Immune complex‐induced neutrophil functions: A focus on cell death. (22nd May 2018) - Vermeren, Sonja; Karmakar, Utsa; Rossi, Adriano G.
Abstract: Neutrophils are amongst the first cells to be recruited to sites of infection or trauma. Neutrophil functional responsiveness is tightly regulated by many agents including immune complexes. These immune cells can generate reactive oxygen species and degranulate to release abundant cytotoxic products, making them efficient at killing invading microorganisms. If neutrophil function is dysregulated, however, these cells have the potential to cause unwanted host tissue damage as exemplified by pathological and chronic inflammatory conditions. In physiological inflammation, once the initial insult has efficiently been dealt with, neutrophils are thought to leave the tissues or undergo programmed cells death, especially apoptosis. Apoptotic neutrophils are then rapidly removed by other phagocytes, primarily macrophages, by mechanisms that do not elicit a pro‐inflammatory response. In this review, we discuss the interesting observations and consequences that immune complexes have on neutrophil cell death processes such as apoptosis.